2016
DOI: 10.1002/masy.201500138
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Gelators Bearing Electroactive Groups as Cathode Materials for Rechargeable Batteries

Abstract: Summary: Low molecular weight gelators bearing 2,2,6,6-tetramethyl-piperidine-1-oxyl (TEMPO) were synthesized and demonstrated to have reversible electrochemical redox properties. The gelation tests showed that the compounds have excellent gelation properties in g-butyrolactone and propylene carbonate. Atomic force microscopy and transmission electron microscopy images showed the 3D network fibrous structure with an average diameter of 20-50 nm. Fast and reversible charge storage capabilities were established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the literature, a vast number of papers have shown the possibility to use physical gels in a variety of different fields of industry (in pharmaceutics, medicine, enginery, electronics, etc.). [6][7][8][9][10][11][12][13][14] Moreover our previous studies showed that such ionogels based on LMWGs can have new unexpected properties like enhanced conductivity effects, whose origin constitutes an open question that needs to be answered if these materials are going to be a real candidate for replacing PGEs. 15 Both mentioned approaches can deliver solidified electrolytes, the former are created by covalent interactions, the latter by physical ones.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, a vast number of papers have shown the possibility to use physical gels in a variety of different fields of industry (in pharmaceutics, medicine, enginery, electronics, etc.). [6][7][8][9][10][11][12][13][14] Moreover our previous studies showed that such ionogels based on LMWGs can have new unexpected properties like enhanced conductivity effects, whose origin constitutes an open question that needs to be answered if these materials are going to be a real candidate for replacing PGEs. 15 Both mentioned approaches can deliver solidified electrolytes, the former are created by covalent interactions, the latter by physical ones.…”
Section: Introductionmentioning
confidence: 99%
“…The small molecules are designed to stack via noncovalent interactions, such as hydrogen bonding and π–π stacking. , Compared with chemically cross-linked gels, the supramolecular compounds are loosely connected and thus offer a larger diffusion coefficient of D app = 10 –7 cm 2 /s . TEMPO and nitronyl nitroxide gelators have been reported, , whereas larger redox moieties would disrupt the supramolecular interactions that form gels . It is unclear whether the gels themselves or trace amounts of dissolved gelators contributed to the large diffusion coefficient. , …”
Section: Redox Processes Of Organic Robust Radicals and Their Polymersmentioning
confidence: 99%
“…The growing significance of the physical gels can be observed on the basis of their practical applications in a variety of different fields of industry (in pharmaceutics, medicine, enginery, electronics, etc.) [9][10][11][12][13][14][15][16][17]. In case of the ionogels, the weakest point is low phase transition temperature (even much below 100°C) what makes them lose with PGE, even if using polymers have some drawbacks (e.g., disposal of used elements).…”
Section: Introductionmentioning
confidence: 99%